Determinan Pertumbuhan Ekonomi Di Indonesia - Early Ridho Kismawadi; Oktavializa Oktavializa; Abdul Hamid (Universitas Muhammadiyah Surabaya, 2021)
This research has the formulation of the problem namely, the first is how the influence of murabaha financing on economic growth in Indonesia, the second is how the influence of mudharabah financing on economic growth in Indonesia, the third is how the influence of ijarah financing on economic growth in Indonesia, and the fourth how is the influence of murabaha financing , mudaraba and ijarah on economic growth in Indonesia.This study aims to determine the effect of murabahah, mudharabah and ijarah financing on economic growth in Indonesia. In this study only 14 years were taken. This research uses quantitative research methods. The technique used in this study is Purposive Sampling, which is a technique of deliberate sampling. The type of data used in this study is secondary. Data analysis techniques used in this study are the analysis of classic assumptions, multiple linear regression, and hypotheses. Partial results (T test) the influence of murabaha financing (X1) of 0.026 <0.05, mudharabah financing (X2) of 0.023 <0.05, ijarah financing (X3) of 0.010 <0.05 and a positive and significant effect on economic growth in Indonesia. F test results (Simultaneous) showed a significant value of 0.002 <0.05, which means that murabahah, mudharabah and ijarah financing simultaneously had a significant effect on economic growth in Indonesia. Then from the R-square test results of 0.62 or 62.3%. The magnitude of these results can be explained by the murabaha, mudharabah and ijarah financing variables in this study, while the remaining 37.7% is explained by other variables not included in this study